Preparation method of low-temperature-resistant lithium ion energy storage battery and prepared battery

The preparation of carbon-coated manganese-doped lithium iron phosphate batteries through hydrothermal method solves the problem of electrochemical performance degradation of lithium-ion batteries in low-temperature environments, and achieves efficient low-temperature electrochemical performance and stability.

CN119725761AActive Publication Date: 2025-03-28RAILWAY CONSTR RES INST OF CHINA ACAD OF RAILWAY SCI CO LTD +1
View PDF 10 Cites 0 Cited by

Patent Information

Application Number
CN202411543608.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-31
Publication Date
2025-03-28
Estimated Expiration
2044-10-31

AI Technical Summary

Technical Problem

Existing lithium-ion batteries show deterioration or failure of electrochemical properties in low temperature environments, resulting in limited applications in high-altitude and cold areas.

Method used

Carbon-coated manganese-doped lithium iron phosphate batteries were prepared by hydrothermal method, and the electrical contact and conductivity of the material were improved by carbon coating, and the rate performance and conductivity of the material were improved by doping manganese ions.

Benefits of technology

It realizes excellent electrochemical performance and stability of lithium-ion energy storage batteries in low temperature environments, improves the charge and discharge specific capacity and cycle performance, and is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119725761A_ABST
    Figure CN119725761A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of a low-temperature-resistant lithium ion energy storage battery and the prepared battery. The preparation method comprises the following steps: dissolving an iron source, a manganese source, a phosphorus source and ascorbic acid in deionized water, and uniformly mixing to obtain a first solution; dissolving a lithium source in deionized water, and uniformly mixing to obtain a second solution; dropwise adding the second solution into the first solution at a constant speed, uniformly stirring and mixing to obtain a mixed solution, and carrying out superfine grinding treatment on the mixed solution to obtain first slurry; carrying out constant-temperature reaction on the first slurry, and then carrying out suction filtration washing and vacuum drying to obtain a precursor; and grinding and uniformly mixing the precursor, a carbon source, conductive carbon black and graphene oxide, carrying out refining treatment to obtain second slurry, and sintering the second slurry in a N2 environment in stages to obtain the low-temperature-resistant lithium ion energy storage battery. The battery is prepared by the preparation method. The material has excellent charge-discharge specific capacity, good cycle performance and excellent low-temperature electrochemical performance, is simple to prepare and is suitable for industrial production.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of lithium ion batteries, and in particular to a method for preparing a low-temperature resistant lithium ion energy storage battery and the prepared battery. Background Art

[0002] There are often a large number of high and steep slope projects along the railways in plateau and cold regions. The dynamic effects of earthquakes, freeze-thaw, rainfall, etc. are prominent, which can easily induce serious engineering disasters. Carrying out long-term automated monitoring of slope stability is of great significance to ensuring the safety of on-site construction and line operation. The power consumption of monitoring systems of different types and frequencies varies greatly, and the energy supply batteries used are also different. However, in the face of low temperature conditions or even ultra-low temperature conditions in plateau and cold regions, most batteries cannot meet the daily power demand of the monitoring system. The common batteries in today's plateau and cold regions are mainly lithium-ion batteries, and lithium-ion batteries are divided into three types: lithium manganese oxide batteries, lithium iron phosphate batteries, and ternary lithium-ion batteries.

[0003] Lithium manganese oxide battery cathode materials have many advantages such as high safety and good low temperature performance, but the cathode materials themselves are not stable and easily decompose to produce gas. They are often mixed with other materials to reduce the cost of the battery cell, but their cycle life decays quickly, they are prone to swelling, have poor high temperature performance, and have a relatively short life, which has certain application limitations. Due to its high energy density, the charge and discharge specific capacity of ternary lithium-ion batteries is relatively high, but there is a common O 2- Oxidation of Ni 2+ / Li + There are many problems such as mixed cations and easy side reactions of surface alkaline oxides, resulting in poor cycle stability and certain limitations on application.

[0004] Compared with the above two batteries, lithium iron phosphate batteries have many advantages such as good thermal stability, low cost, and long life. However, the low-temperature charging and discharging performance of lithium iron phosphate materials is poor. When the temperature is below 0°C, the energy conversion and storage capacity of lithium-ion batteries decay rapidly at low temperatures (below 0°C), causing battery performance degradation or failure, which seriously hinders the promotion and development of lithium-ion batteries, increases the cost and risk of using lithium-ion batteries, and reduces energy utilization. Therefore, improving the low-temperature performance of lithium iron phosphate is the key to improving its electrochemical performance.

[0005] Chinese patent CN106340624A "A method for preparing carbon-coated lithium iron phosphate nanorods" discloses a carbon-coated lithium iron phosphate nanorod, which improves the electrochemical performance of lithium iron phosphate at low temperatures by coating carbon on the surface of lithium iron phosphate. However, the carbon-coated lithium iron phosphate nanorod has a low discharge specific capacity and general cycle performance, and its low-temperature electrochemical performance needs to be further improved.

[0006] Therefore, it is of great significance to develop a lithium-ion energy storage battery with high discharge specific capacity, good cycle performance, and excellent low-temperature electrochemical performance, as well as a preparation method and application thereof. Summary of the invention

[0007] The object of the present invention is to provide a method for preparing a low-temperature resistant lithium-ion energy storage battery and the battery prepared, which is used to solve at least one of the above technical problems. The battery has excellent charge and discharge specific capacity, good cycle performance, excellent low-temperature electrochemical performance, simple preparation, and is suitable for industrial production.

[0008] The embodiment of the present invention is achieved as follows:

[0009] A method for preparing a low-temperature resistant lithium-ion energy storage battery, comprising:

[0010] S100, dissolving an iron source, a manganese source, a phosphorus source and ascorbic acid in deionized water, and mixing them evenly to obtain a first solution.

[0011] S200, dissolving the lithium source in deionized water and mixing the mixture evenly to obtain a second solution.

[0012] S300, adding the second solution dropwise into the first solution at a uniform speed, stirring and mixing to obtain a mixed solution, and performing ultrafine grinding on the mixed solution to obtain a first slurry.

[0013] S400, the first slurry is subjected to a constant temperature reaction at 200° C. to 220° C., and then filtered, washed, and vacuum dried to obtain a precursor.

[0014] S500, grinding and mixing the precursor, carbon source, conductive carbon black and graphene oxide uniformly, and refining the mixture to obtain a second slurry, and sintering the second slurry in sections in a N2 environment to obtain a low-temperature resistant lithium-ion energy storage battery.

[0015] In a preferred embodiment of the present invention, in the method for preparing the low-temperature resistant lithium-ion energy storage battery, the iron source includes at least one of iron oxide, iron sulfate, iron phosphate, ferrous oxalate, and iron nitrate.

[0016] The manganese source includes at least one of manganese dioxide, manganese tetraoxide and manganese acetate.

[0017] The phosphorus source includes at least one of phosphoric acid, monoammonium hydrogen phosphate, and diammonium dihydrogen phosphate.

[0018] The lithium source includes at least one of lithium hydroxide, lithium acetate, lithium carbonate, lithium nitrate and lithium fluoride.

[0019] Its technical effects are: iron oxide provides high stability, iron sulfate and iron nitrate are easily soluble in water, ferrous oxalate and iron phosphate provide good electrochemical performance; manganese dioxide and manganese tetraoxide provide excellent conductivity and stability, manganese acetate has good solubility and reactivity; lithium hydroxide and lithium carbonate are often used to improve the stability of materials, and lithium nitrate and lithium fluoride help improve low-temperature performance and conductivity. Through the synergistic effect of different compounds, the electrochemical performance and structural stability of the electrode material are effectively improved, so that the prepared lithium-ion energy storage battery still has good electrochemical performance and stability in low-temperature environments.

[0020] In a preferred embodiment of the present invention, in the method for preparing the above-mentioned low-temperature resistant lithium-ion energy storage battery, in the first solution, the molar ratio of iron element to ascorbic acid is Fe:C6H8O6=1:(0.4-0.6).

[0021] The technical effect is that by adjusting the molar ratio of iron element and ascorbic acid, the growth rate of the precursor particles and the final particle size are controlled, particles with ideal size and morphology can be generated, ascorbic acid is ensured to be evenly distributed in the solution, the even distribution and dissolution of the iron source are promoted, and the iron source is prevented from aggregating or precipitating in the solution.

[0022] In a preferred embodiment of the present invention, in the method for preparing the low-temperature resistant lithium-ion energy storage battery, the molar ratio of lithium, iron, manganese and phosphorus in the mixed solution is Li:Fe:Mn:P=3:0.96:0.04:1.

[0023] The technical effects are: ensuring that the positive electrode material has an appropriate crystal structure and electrochemical activity, taking into account the conductivity and stability of the material; the appropriate amount of Mn incorporation helps to reduce the charge transfer impedance of the material and enhance the discharge capacity and efficiency of the battery at low temperatures; the appropriate Li:Fe:Mn molar ratio helps to form a favorable crystal structure, optimize the migration path of lithium ions, and increase the diffusion rate of lithium ions; the ratio of Fe and P is close to 1:1, and the ratio of Li is 3, which can form a stable lithium iron phosphate structure (LiFePO4) with high stability and safety. At the same time, a small amount of Mn doping (0.04) will not destroy this stable structure, further enhancing the overall stability of the material and reducing capacity decay.

[0024] In a preferred embodiment of the present invention, in the method for preparing the low-temperature resistant lithium-ion energy storage battery, in S300, the second solution and the first solution are stirred for 10 minutes to 30 minutes.

[0025] The median particle diameter (D50) of the first slurry obtained after ultrafine grinding is 80nm-100nm.

[0026] The technical effect is to optimize the uniformity and particle size of the slurry. Nano-scale particles (80nm-100nm) can provide a shorter lithium ion migration path, reduce the internal resistance of the battery, and improve the discharge efficiency of the battery.

[0027] In a preferred embodiment of the present invention, in the method for preparing the low-temperature resistant lithium-ion energy storage battery, in S400, the time for the constant temperature reaction of the first slurry is 12 hours.

[0028] The vacuum drying temperature is between 60°C and 80°C, and the time is between 2h and 3h.

[0029] Its technical effects are: long-term constant temperature reaction helps to form a uniform precursor particle structure, ensure the consistency of the chemical composition and crystal structure of the material, fully remove impurities in the precursor, and improve the purity of the material; controlling the drying conditions can effectively remove moisture and residual solvents in the material, ensure that the material is dried evenly, avoid the appearance of bubbles and holes in the subsequent sintering process, and avoid material aging caused by too much time.

[0030] In a preferred embodiment of the present invention, in the method for preparing the low-temperature resistant lithium-ion energy storage battery, the carbon source includes at least one of glucose, fructose, white sugar, citric acid, sucrose, and activated carbon.

[0031] The technical effect is that glucose, fructose, white sugar, sucrose, etc. can be decomposed and carbonized under high temperature conditions to form a conductive carbon network, which can effectively improve the conductivity of the electrode material and promote the rapid transmission of electrons; the carbon layer can improve the structural stability of the material and increase the cycle life of the battery.

[0032] In a preferred embodiment of the present invention, in the preparation method of the above-mentioned low-temperature resistant lithium-ion energy storage battery, in the second slurry, the mass ratio of the precursor, carbon source, conductive carbon black and graphene oxide is precursor: carbon source: conductive carbon black: graphene oxide = 1: (0.04-0.06): 0.02: 0.03.

[0033] Its technical effect is: by optimizing the mass ratio of precursor, carbon source, conductive carbon black and graphene oxide, it can effectively improve the conductivity, structural stability and low-temperature performance of electrode materials, and significantly improve the overall electrochemical performance and cycle life of low-temperature resistant lithium-ion energy storage batteries.

[0034] In a preferred embodiment of the present invention, in the above-mentioned method for preparing a low-temperature resistant lithium-ion energy storage battery, in S500, the median particle diameter (D50) of the second slurry obtained after the refinement treatment is 40nm to 50nm.

[0035] The conditions for the staged sintering are to keep the temperature at 200°C for 3 hours, then raise the temperature to 700°C and sinter for 5 to 7 hours.

[0036] The technical effect is that after the second slurry is refined, the median diameter (D50) of the particles is 40nm to 50nm, which helps to increase the specific surface area of ​​the material, increase the contact area between the electrode material and the electrolyte, increase the rate of electrode reaction and the energy density of the battery, reduce the diffusion path of lithium ions in the electrode material, promote the rapid diffusion of lithium ions and the efficient conduction of electrons, and improve the charge and discharge rate and power performance of the battery. The precisely controlled sintering process can reduce the pores and defects inside the material, enable the material particles to be tightly combined, and ensure the structural uniformity and stability of the electrode material.

[0037] A low-temperature resistant lithium-ion energy storage battery is prepared by the above-mentioned preparation method of the low-temperature resistant lithium-ion energy storage battery.

[0038] The beneficial effects of the present invention are:

[0039] The present invention prepares a carbon-coated manganese-doped lithium iron phosphate battery by a hydrothermal method. The carbon coating can effectively prevent the oxidation of Fe in the lithium iron phosphate material and improve the electrical contact between the materials. The addition of conductive carbon black and graphene oxide to the carbon source can further improve the electronic conductivity of the material, so that the electrons gained and lost during the electrochemical reaction can be conducted in time, which effectively improves the electrochemical performance of the lithium ion energy storage battery. The doping of manganese ions unequally replaces the Fe position in the lithium iron phosphate, which can promote the generation of favorable defects in the lattice of the material, widen the diffusion channel of Li ions, reduce the resistance of Li ions to diffuse along a one-dimensional path, and improve the diffusion kinetics of Li ions in the lattice, thereby improving the rate performance of the material and reducing the resistance. Improve the conductivity and charge-discharge specific capacity of the material; through ultrafine grinding treatment, the contact area between materials can be effectively increased, so that magnesium ions can be fully dispersed and doped into lithium iron phosphate, and the active sites of the reaction are increased, the specific surface area of ​​the material is increased, and the cyclic reversibility and low-temperature performance of the material are improved. Then, through refinement treatment, the carbon layer can be fully coated on the surface of the particles, hindering the further growth of the particles, reducing the contact area between the particles, reducing the possibility of agglomeration between the particles, inhibiting the pulverization of the material under high-rate charge and discharge, and avoiding the self-discharge phenomenon that is easy to occur in nano-scale lithium iron phosphate as much as possible, and finally obtaining a lithium-ion energy storage battery with excellent charge-discharge specific capacity, good cycle performance, and excellent low-temperature electrochemical performance. BRIEF DESCRIPTION OF THE DRAWINGS

[0040] In order to more clearly illustrate the technical solutions of the embodiments of the present invention, the drawings required for use in the embodiments are briefly introduced below. It should be understood that the following drawings only show certain embodiments of the present invention and therefore should not be regarded as limiting the scope. For ordinary technicians in this field, other related drawings can be obtained based on these drawings without creative work.

[0041] Figure 1a A schematic diagram of the cycle performance and coulomb efficiency curve at -20°C and 0.5C of Example 1 of the method for preparing a low-temperature-resistant lithium-ion energy storage battery of the present invention;

[0042] Figure 1b A schematic diagram of the cycle performance and coulombic efficiency curve at -20°C and 1C of Example 1 of the method for preparing a low-temperature-resistant lithium-ion energy storage battery of the present invention;

[0043] Figure 2a A schematic diagram of the cycle performance and coulombic efficiency curve at -40°C and 0.5C of Example 1 of the method for preparing a low-temperature-resistant lithium-ion energy storage battery of the present invention;

[0044] Figure 2b A schematic diagram of the cycle performance and coulomb efficiency curve at -40°C and 0.5C of Comparative Example 1 of the preparation method of the low-temperature resistant lithium-ion energy storage battery of the present invention;

[0045] Figure 3a This is a schematic diagram of the charge and discharge curves at -40°C and 0.5C of Example 1 of the method for preparing a low-temperature-resistant lithium-ion energy storage battery of the present invention;

[0046] Figure 3b This is a schematic diagram of the charge and discharge curves at -40°C and 0.5C of Comparative Example 1 of the preparation method of the low-temperature resistant lithium-ion energy storage battery of the present invention. DETAILED DESCRIPTION

[0047] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below in conjunction with the drawings in the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Generally, the components of the embodiments of the present invention described and shown in the drawings here can be arranged and designed in various different configurations.

[0048] An embodiment of the present invention provides a preparation method of a low-temperature resistant lithium-ion energy storage battery, which includes: S100, dissolving an iron source, a manganese source, a phosphorus source and ascorbic acid in deionized water, mixing them evenly, and obtaining a first solution; S200, dissolving a lithium source in deionized water, mixing them evenly, and obtaining a second solution; S300, uniformly adding the second solution to the first solution, stirring and mixing them evenly, obtaining a mixed solution, and ultrafine grinding the mixed solution to obtain a first slurry; S400, the first slurry is subjected to a constant temperature reaction at 200° C. to 220° C., and then filtered and washed, and vacuum dried to obtain a precursor; S500, grinding and mixing the precursor and a carbon source, conductive carbon black, and graphene oxide evenly, and refining them to obtain a second slurry, and sintering the second slurry in stages in an N2 environment to obtain a low-temperature resistant lithium-ion energy storage battery.

[0049] The iron source includes at least one of iron oxide, iron sulfate, iron phosphate, ferrous oxalate, and iron nitrate; the manganese source includes at least one of manganese dioxide, manganese tetraoxide, and manganese acetate; the phosphorus source includes at least one of phosphoric acid, monoammonium hydrogen phosphate, and diammonium hydrogen phosphate; the lithium source includes at least one of lithium hydroxide, lithium acetate, lithium carbonate, lithium nitrate, and lithium fluoride.

[0050] Its technical effects are: iron oxide provides high stability, iron sulfate and iron nitrate are easily soluble in water, ferrous oxalate and iron phosphate provide good electrochemical performance; manganese dioxide and manganese tetraoxide provide excellent conductivity and stability, manganese acetate has good solubility and reactivity; lithium hydroxide and lithium carbonate are often used to improve the stability of materials, and lithium nitrate and lithium fluoride help improve low-temperature performance and conductivity. Through the synergistic effect of different compounds, the electrochemical performance and structural stability of the electrode material are effectively improved, so that the prepared lithium-ion energy storage battery still has good electrochemical performance and stability in low-temperature environments.

[0051] In the first solution, the molar ratio of iron element to ascorbic acid is Fe:C6H8O6=1:(0.4-0.6).

[0052] The technical effect is that by adjusting the molar ratio of iron element and ascorbic acid, the growth rate of the precursor particles and the final particle size are controlled, particles with ideal size and morphology can be generated, ascorbic acid is ensured to be evenly distributed in the solution, the even distribution and dissolution of the iron source are promoted, and the iron source is prevented from aggregating or precipitating in the solution.

[0053] In the mixed solution, the molar ratio of lithium, iron, manganese and phosphorus is Li:Fe:Mn:P=3:0.96:0.04:1.

[0054] The technical effects are: ensuring that the positive electrode material has an appropriate crystal structure and electrochemical activity, taking into account the conductivity and stability of the material; the appropriate amount of Mn incorporation helps to reduce the charge transfer impedance of the material and enhance the discharge capacity and efficiency of the battery at low temperatures; the appropriate Li:Fe:Mn molar ratio helps to form a favorable crystal structure, optimize the migration path of lithium ions, and increase the diffusion rate of lithium ions; the ratio of Fe and P is close to 1:1, and the ratio of Li is 3, which can form a stable lithium iron phosphate structure (LiFePO4) with high stability and safety. At the same time, a small amount of Mn doping (0.04) will not destroy this stable structure, further enhancing the overall stability of the material and reducing capacity decay.

[0055] In S300, the second solution and the first solution are stirred for 10 to 30 minutes; the median particle diameter (D50) of the first slurry obtained after ultrafine grinding is 80 nm to 100 nm.

[0056] The technical effect is to optimize the uniformity and particle size of the slurry. Nano-scale particles (80nm-100nm) can provide a shorter lithium ion migration path, reduce the internal resistance of the battery, and improve the discharge efficiency of the battery.

[0057] In S400, the first slurry is subjected to constant temperature reaction for 12 hours; the vacuum drying temperature is between 60° C. and 80° C. for 2 hours to 3 hours.

[0058] Its technical effects are: long-term constant temperature reaction helps to form a uniform precursor particle structure, ensure the consistency of the chemical composition and crystal structure of the material, fully remove impurities in the precursor, and improve the purity of the material; controlling the drying conditions can effectively remove moisture and residual solvents in the material, ensure that the material is dried evenly, avoid the appearance of bubbles and holes in the subsequent sintering process, and avoid material aging caused by too much time.

[0059] The carbon source includes at least one of glucose, fructose, white sugar, citric acid, sucrose and activated carbon.

[0060] The technical effect is that glucose, fructose, white sugar, sucrose, etc. can be decomposed and carbonized under high temperature conditions to form a conductive carbon network, which can effectively improve the conductivity of the electrode material and promote the rapid transmission of electrons; the carbon layer can improve the structural stability of the material and increase the cycle life of the battery.

[0061] In the second slurry, the mass ratio of the precursor, the carbon source, the conductive carbon black and the graphene oxide is precursor: carbon source: conductive carbon black: graphene oxide = 1: (0.04-0.06): 0.02: 0.03.

[0062] Its technical effect is: by optimizing the mass ratio of precursor, carbon source, conductive carbon black and graphene oxide, it can effectively improve the conductivity, structural stability and low-temperature performance of electrode materials, and significantly improve the overall electrochemical performance and cycle life of low-temperature resistant lithium-ion energy storage batteries.

[0063] In S500, the median diameter (D50) of the particles of the second slurry obtained after the refinement treatment is 40nm-50nm; the conditions for the staged sintering are: keeping at 200°C for 3h, raising the temperature to 700°C, and sintering for 5h-7h.

[0064] The technical effect is that after the second slurry is refined, the median diameter (D50) of the particles is 40nm to 50nm, which helps to increase the specific surface area of ​​the material, increase the contact area between the electrode material and the electrolyte, increase the rate of electrode reaction and the energy density of the battery, reduce the diffusion path of lithium ions in the electrode material, promote the rapid diffusion of lithium ions and the efficient conduction of electrons, and improve the charge and discharge rate and power performance of the battery. The precisely controlled sintering process can reduce the pores and defects inside the material, enable the material particles to be tightly combined, and ensure the structural uniformity and stability of the electrode material.

[0065] The present invention also provides a low-temperature resistant lithium-ion energy storage battery, which is prepared by the preparation method of the low-temperature resistant lithium-ion energy storage battery as described above.

[0066] To better illustrate the purpose, technical scheme and advantages of the present invention, the present invention is further described by the following examples. All raw materials can be obtained from commercial sources; unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0067] Example 1

[0068] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0069] (1) dissolving 4.8 mmol of ferric sulfate, 0.2 mmol of manganese dioxide, 5 mmol of phosphoric acid and 2.5 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0070] (2) dissolving 15 mmol of lithium acetate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to obtain a mixed solution;

[0071] (3) The obtained mixed solution was ultrafinely ground to a particle size of 80-100 nm in slurry 1, reacted at 220° C. for 12 h, filtered and washed, and vacuum dried at 60° C. for 3 h to obtain a precursor;

[0072] (4) Grind and mix 5 g of the obtained precursor with 20 mg of glucose, 10 mg of conductive carbon black, and 15 mg of graphene oxide, and refine the mixture until the particle D50 of slurry 2 is 40-50 nm. Sinter the mixture in stages under the protection of N2, keep the temperature at 200°C for 3 h, then heat the mixture to 700°C and sinter for 5 h to obtain the lithium-ion energy storage battery.

[0073] Example 2

[0074] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0075] (1) dissolving 4.8 mmol of iron oxide, 0.2 mmol of manganese tetraoxide, 5 mmol of ammonium monohydrogen phosphate and 2 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0076] (2) dissolving 15 mmol of lithium carbonate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to mix well to obtain a mixed solution;

[0077] (3) The obtained mixed solution was ultrafinely ground to a particle size of slurry 1 of 80-100 nm, reacted at 200° C. for 12 h, filtered and washed, and vacuum dried at 80° C. for 2 h to obtain a precursor;

[0078] (4) Grind and mix 5 g of the obtained precursor with 25 mg of glucose, 10 mg of conductive carbon black, and 15 mg of graphene oxide, and refine the mixture until the particle D50 of slurry 2 is 40-50 nm. Sinter the mixture in stages under the protection of N2, keep the temperature at 200°C for 3 h, then heat the mixture to 700°C and sinter for 6 h to obtain the lithium-ion energy storage battery.

[0079] Example 3

[0080] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0081] (1) dissolving 4.8 mmol of ferrous oxalate, 0.2 mmol of manganese acetate, 5 mmol of diammonium phosphate and 3 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0082] (2) dissolving 15 mmol of lithium nitrate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to mix well to obtain a mixed solution;

[0083] (3) The obtained mixed solution was ultrafinely ground to a particle size of 80-100 nm in slurry 1, reacted at 210° C. for 12 h, filtered and washed, and vacuum dried at 70° C. for 2 h to obtain a precursor;

[0084] (4) Grind and mix 5 g of the obtained precursor with 30 mg of glucose, 10 mg of conductive carbon black, and 15 mg of graphene oxide, and refine the mixture until the particle D50 of slurry 2 is 40-50 nm. Sinter the mixture in stages under the protection of N2, keep the temperature at 200°C for 3 h, then raise the temperature to 700°C and sinter for 7 h to obtain the lithium-ion energy storage battery.

[0085] Comparative Example 1

[0086] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0087] (1) dissolving 5 mmol of ferric sulfate, 5 mmol of phosphoric acid and 2.5 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0088] (2) dissolving 15 mmol of lithium acetate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to obtain a mixed solution;

[0089] (3) reacting the obtained mixed solution at 220° C. for 12 h, filtering and washing, and vacuum drying at 60° C. for 3 h to obtain a precursor;

[0090] (4) Grind and mix 5 g of the obtained precursor with 20 mg of glucose, 10 mg of conductive carbon black, and 15 mg of graphene oxide, and sinter them in stages under the protection of N2. After keeping the temperature at 200°C for 3 h, raise the temperature to 700°C and sinter for 5 h to obtain the lithium-ion energy storage battery.

[0091] Compared with Example 1, this comparative example only performs carbon coating.

[0092] Comparative Example 2

[0093] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0094] (1) dissolving 4.8 mmol of ferric sulfate, 0.2 mmol of manganese dioxide, 5 mmol of phosphoric acid and 2.5 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0095] (2) dissolving 15 mmol of lithium acetate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to obtain a mixed solution;

[0096] (3) The obtained mixed solution is ultrafinely ground until the D50 of the slurry 1 particles is 80-100 nm, the mixture is reacted at a constant temperature of 220° C. for 12 h, filtered and washed, and vacuum dried at 60° C. for 3 h to obtain the lithium-ion energy storage battery.

[0097] Compared with Example 1, this comparative example does not undergo carbon coating.

[0098] Comparative Example 3

[0099] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0100] (1) dissolving 5 mmol of ferric sulfate, 5 mmol of phosphoric acid and 2.5 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0101] (2) dissolving 15 mmol of lithium acetate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to obtain a mixed solution;

[0102] (3) The obtained mixed solution was ultrafinely ground to a particle size of 80-100 nm in slurry 1, reacted at 220° C. for 12 h, filtered and washed, and vacuum dried at 60° C. for 3 h to obtain a precursor;

[0103] (4) Grind and mix 5 g of the obtained precursor with 20 mg of glucose, 10 mg of conductive carbon black, and 15 mg of graphene oxide, and refine the mixture until the particle D50 of slurry 2 is 40-50 nm. Sinter the mixture in stages under the protection of N2, keep the temperature at 200°C for 3 h, then heat the mixture to 700°C and sinter for 5 h to obtain the lithium-ion energy storage battery.

[0104] Compared with Example 1, this comparative example does not contain a manganese source, and the insufficient part is supplemented by an iron source component.

[0105] Comparative Example 4

[0106] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0107] (1) dissolving 4.8 mmol of ferric sulfate, 0.2 mmol of manganese dioxide, 5 mmol of phosphoric acid and 2.5 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0108] (2) dissolving 15 mmol of lithium acetate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to obtain a mixed solution;

[0109] (3) reacting the obtained mixed solution at 220° C. for 12 h, filtering and washing, and vacuum drying at 60° C. for 3 h to obtain a precursor;

[0110] (4) Grind and mix 5 g of the obtained precursor with 20 mg of glucose, 10 mg of conductive carbon black, and 15 mg of graphene oxide, and refine the mixture until the particle D50 of slurry 2 is 40-50 nm. Sinter the mixture in stages under the protection of N2, keep the temperature at 200°C for 3 h, then heat the mixture to 700°C and sinter for 5 h to obtain the lithium-ion energy storage battery.

[0111] Compared with Example 1, this comparative example does not undergo ultrafine grinding.

[0112] Comparative Example 5

[0113] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0114] (1) dissolving 4.8 mmol of ferric sulfate, 0.2 mmol of manganese dioxide, 5 mmol of phosphoric acid and 2.5 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0115] (2) dissolving 15 mmol of lithium acetate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to obtain a mixed solution;

[0116] (3) The obtained mixed solution was ultrafinely ground to a particle size of 80-100 nm in slurry 1, reacted at 220° C. for 12 h, filtered and washed, and vacuum dried at 60° C. for 3 h to obtain a precursor;

[0117] (4) Grind and mix 5 g of the obtained precursor with 20 mg of glucose, 10 mg of conductive carbon black, and 15 mg of graphene oxide, and sinter them in stages under the protection of N2. After keeping the temperature at 200°C for 3 h, raise the temperature to 700°C and sinter for 5 h to obtain the lithium-ion energy storage battery.

[0118] Compared with Example 1, this comparative example does not undergo refinement.

[0119] Comparative Example 6

[0120] A method for preparing a lithium-ion energy storage battery comprises the following steps:

[0121] (1) dissolving 4.8 mmol of ferric sulfate, 0.2 mmol of manganese dioxide, 5 mmol of phosphoric acid and 2.5 mmol of ascorbic acid in 30 mL of deionized water and mixing well to obtain a first solution;

[0122] (2) dissolving 15 mmol of lithium acetate in 20 mL of deionized water, mixing well to obtain a second solution, and uniformly adding the second solution dropwise to the first solution, stirring for 20 min to obtain a mixed solution;

[0123] (3) reacting the obtained mixed solution at 220° C. for 12 h, filtering and washing, and vacuum drying at 60° C. for 3 h to obtain a precursor;

[0124] (4) Grind and mix 5 g of the obtained precursor with 20 mg of glucose, 10 mg of conductive carbon black, and 15 mg of graphene oxide, and sinter them in stages under the protection of N2. After keeping the temperature at 200°C for 3 h, raise the temperature to 700°C and sinter for 5 h to obtain the lithium-ion energy storage battery.

[0125] Compared with Example 1, this comparative example does not undergo ultrafine grinding and refining treatment.

[0126] The above samples were subjected to performance tests, and the specific test process included: using the materials prepared in each embodiment and comparative example as the positive electrode sheet, graphite as the negative electrode, adding propylene carbonate, vinyl sulfate, and lithium difluorophosphate into the low-temperature electrolyte, and testing the electrochemical performance of the battery.

[0127] like Figure 1a and Figure 1b As shown, the first cycle discharge capacity of Example 1 of the present invention at -20°C and 0.5C is 163.1mAh / g, the first cycle coulomb efficiency is 96.38%, the discharge capacity after 48 cycles is 166.6mAh / g, and the capacity retention rate is 102%. Due to incomplete activation, the capacity increased slightly in the first five cycles of charge and discharge tests, and the capacity retention rate was finally greater than 1. The first cycle discharge capacity at 1C is 147.8mAh / g, and the discharge capacity gradually increases to a flat level before 100 cycles. The first cycle coulomb efficiency is 88.9%. As the number of cycles increases, the coulomb efficiency remains at 99%. The discharge capacity is 163.6mAh / g at the 120th cycle, and reaches 163.3mAh / g at the 320th cycle, with a retention rate of 110%. This may be due to the fact that the activation degree of the battery increases continuously in the first 100 cycles, and the discharge capacity also increases accordingly.

[0128] The low temperature cycle performance of Example 1 and Comparative Example 1 was tested at -40°C and 0.5°C. Figure 2a and Figure 2b As shown, the first cycle discharge capacity and coulomb efficiency of Example 1 are 79.23mAh / g and 102.02% respectively, and the capacity and coulomb efficiency after 50 cycles are 71.82mAh / g and 100.05% respectively, and the capacity retention rate is 90.66%. The first cycle discharge capacity and coulomb efficiency of Comparative Example 1 are 55.60mAh / g and 154.87% respectively, and the capacity and coulomb efficiency after 50 cycles are 42.44mAh / g and 100.02% respectively, and the capacity retention rate is 76.33%; the capacity and coulomb efficiency after 100 cycles are 38.68mAh / g and 99.98% respectively, and the capacity retention rate is 69.57%.

[0129] At the same time, the charge and discharge performance of Example 1 and Comparative Example 1 were tested at -40°C and 0.5C. Figure 3a and Figure 3b As shown, the first cycle capacity of Example 1 is 79.23mAh / g, the voltage platform during charging is above 3.5V, and the voltage platform during discharging is above 3.3V; while the first cycle capacity of Comparative Example 1 is 55.60mAh / g, the voltage platform during charging increases and the voltage platform during discharging decreases, the difference in the voltage platform during charging and discharging increases, the polarization degree of the battery is large, and the energy loss is high, so the capacity is reduced to a certain extent.

[0130] The low temperature cycle performance of each embodiment and comparative example is shown in Table 1:

[0131] Table 1 Low temperature cycle performance of Examples 1-3 and Comparative Examples 1-6

[0132]

[0133] As can be seen from Table 1, Examples 1-3 of the present invention have more stable low-temperature cycle performance and discharge specific capacity, and exhibit excellent low-temperature electrochemical performance at low temperatures of -20°C and -40°C. However, Comparative Example 1 was only carbon-coated, and the low-temperature cycle performance was relatively stable, but the discharge specific capacity was low, which could not be compared with the embodiments; Comparative Example 2 was not carbon-coated, and the discharge specific capacity was low and the cycle performance was poor at -20°C, and the electrochemical performance decayed rapidly at -40°C and could not be tested; Comparative Example 3 was not ion-doped, and the discharge specific capacity was low; Comparative Example 4 was not ultrafinely ground, and the battery performance dropped rapidly after 100 cycles; Comparative Example 5 was not refined, and the battery cycle stability was poor; and Comparative Example 6 was not ultrafinely ground and refined, and the low-temperature cycle performance of the battery was greatly reduced compared with the embodiments.

[0134] The embodiment of the present invention aims to provide a method for preparing a low-temperature resistant lithium-ion energy storage battery and the prepared battery, which has the following effects:

[0135] 1. Carbon-coated manganese-doped lithium iron phosphate batteries were prepared by a hydrothermal method. Carbon coating prevented the oxidation of Fe in the lithium iron phosphate material, improved the electrical contact between the materials, and increased the electronic conductivity of the material, effectively improving the low-temperature electrochemical performance of the lithium-ion energy storage battery.

[0136] 2. The doping of manganese ions unequally replaces the Fe position in lithium iron phosphate, improves the rate performance of the material, reduces resistance, and increases the conductivity and charge-discharge specific capacity of the material.

[0137] 3. Through ultrafine grinding treatment, the contact area between materials can be effectively increased, so that magnesium ions can be fully dispersed and doped into lithium iron phosphate, and the active sites of the reaction are increased, the specific surface area of ​​the material is increased, and the cyclic reversibility and low-temperature performance of the material are improved. Then, through refinement treatment, the carbon layer can be fully coated on the surface of the particles, hindering the further growth of the particles, reducing the contact area between the particles, and reducing the possibility of agglomeration between the particles, thereby obtaining a lithium-ion energy storage battery with excellent charge and discharge specific capacity, good cycle performance, and excellent low-temperature electrochemical performance.

[0138] It should be understood that the above specific embodiments of the present invention are only used to illustrate or explain the principles of the present invention, and do not constitute a limitation of the present invention. Therefore, any modifications, equivalent substitutions, improvements, etc. made without departing from the spirit and scope of the present invention should be included in the protection scope of the present invention. In addition, the appended claims of the present invention are intended to cover all changes and modifications that fall within the scope and boundaries of the appended claims, or the equivalent forms of such scope and boundaries.

Claims

1. A method for preparing a low-temperature resistant lithium-ion energy storage battery, characterized in that: include: S100, dissolving an iron source, a manganese source, a phosphorus source and ascorbic acid in deionized water, and mixing them uniformly to obtain a first solution; S200, dissolving a lithium source in deionized water and mixing the mixture uniformly to obtain a second solution; S300, uniformly adding the second solution to the first solution, stirring and mixing, obtaining a mixed solution, and superfine grinding the mixed solution to obtain a first slurry; S400, the first slurry is subjected to a constant temperature reaction at 200° C. to 220° C., and then filtered, washed, and vacuum dried to obtain a precursor; S500, grinding and mixing the precursor, carbon source, conductive carbon black and graphene oxide uniformly, and refining the mixture to obtain a second slurry, and sintering the second slurry in sections in a N2 environment to obtain a low-temperature resistant lithium-ion energy storage battery.

2. The method for preparing a low-temperature resistant lithium-ion energy storage battery according to claim 1, characterized in that: The iron source includes at least one of iron oxide, iron sulfate, iron phosphate, ferrous oxalate, and iron nitrate; The manganese source includes at least one of manganese dioxide, manganese tetraoxide, and manganese acetate; The phosphorus source includes at least one of phosphoric acid, monoammonium hydrogen phosphate, and diammonium dihydrogen phosphate; The lithium source includes at least one of lithium hydroxide, lithium acetate, lithium carbonate, lithium nitrate and lithium fluoride.

3. The method for preparing a low-temperature resistant lithium-ion energy storage battery according to claim 1, characterized in that: In the first solution, the molar ratio of iron element to ascorbic acid is Fe:C6H8O6=1:(0.4-0.6).

4. The method for preparing a low-temperature resistant lithium-ion energy storage battery according to claim 1, characterized in that: In the mixed solution, the molar ratio of lithium, iron, manganese and phosphorus is Li:Fe:Mn:P=3:0.96:0.04:

1.

5. The method for preparing a low-temperature resistant lithium-ion energy storage battery according to claim 1, characterized in that: In S300, the second solution and the first solution are stirred for 10 min to 30 min; The median particle diameter (D50) of the first slurry obtained after ultrafine grinding is 80nm-100nm.

6. The method for preparing a low-temperature resistant lithium-ion energy storage battery according to claim 1, characterized in that: In S400, the first slurry is subjected to a constant temperature reaction for 12 hours; The vacuum drying temperature is between 60°C and 80°C, and the time is between 2h and 3h.

7. The method for preparing a low-temperature resistant lithium-ion energy storage battery according to claim 1, characterized in that: The carbon source includes at least one of glucose, fructose, white sugar, citric acid, sucrose and activated carbon.

8. The method for preparing a low-temperature resistant lithium-ion energy storage battery according to claim 1, characterized in that: In the second slurry, the mass ratio of the precursor, the carbon source, the conductive carbon black and the graphene oxide is precursor: carbon source: conductive carbon black: graphene oxide = 1: (0.04-0.06): 0.02: 0.

03.

9. The method for preparing a low-temperature resistant lithium-ion energy storage battery according to claim 1, characterized in that: In S500, the median diameter (D50) of the particles of the second slurry obtained after the refinement treatment is 40 nm to 50 nm; The conditions for staged sintering are to keep the temperature at 200°C for 3 hours, then raise the temperature to 700°C and sinter for 5 to 7 hours.

10. A low temperature resistant lithium ion energy storage battery, characterized in that: The low-temperature-resistant lithium-ion energy storage battery is prepared by the preparation method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Positive electrode active material of lithium ion battery, preparation method for positive electrode active material, lithium ion battery positive electrode, and lithium ion battery

    CN105789572A

  • Preparation method of composite carbon-coated nanoscale lithium iron phosphate of three-dimensional network structure

    CN109860572A

  • High-rate lithium iron manganese phosphate composite material, preparation method thereof and lithium ion battery

    CN111559739A

  • Preparation method of high-capacity lithium ferric manganese phosphate material

    CN115072695A

  • Lithium manganese iron phosphate composite material as well as preparation method and application thereof

    CN117855432A